Introducing traceability in an agile development environment Using a systematic methodology for designing and implementing a tailored traceability strategy at 1928 Diagnostics - ORSTADIUS, GABRIEL (My University, 2020)
Software traceability is the ability to interrelate software artifacts, e.g. work products and requirements, and use these relationships to support different software and systems engineering activities such as ensuring product conformance and conducting change impact analysis. Additionally, several regulatory agencies have explicit requirements regarding traceability. To introduce effective traceability, a traceability strategy tailored for the organization’s development process and traceability goals must first be in place, which organizations often struggle with. This action research study aims to show how TracIMo, a methodology for systematically introducing traceability strategies, can be used to design and deploy a tailored traceability strategy. This is done by documenting how TracIMo was used at 1928 Diagnostics, an agile bioinformatics start-up developing infection control products for hospitals, and discussing the benefits, drawbacks, costs and challenges in doing so.
Keywords: Traceability strategy; TracIMo; Agile development environment